Smoking, DNA Methylation, and Breast Cancer: A Mendelian Randomization Study - Tang, Haibo; Yang, Desong; Han, Chaofei; Mu, Ping (Frontiers in Oncology, 2021)
Backgrounds: Smoking was strongly associated with breast cancer in previous studies. Whether smoking promotes breast cancer through DNA methylation remains unknown. Methods: Two-sample Mendelian randomization (MR) analyses were conducted to assess the causal effect of smoking-related DNA methylation on breast cancer risk. We used 436 smoking-related CpG sites extracted from 846 middle-aged women in ARIES project as exposure data. We collected summary data of breast cancer from one of the largest meta-analyses, including 69,501 cases for ER+ breast cancer and 21,468 cases for ER- breast cancer. A total of 485 single nucleotide polymorphisms (SNPs) were selected as instrumental variables (IVs) for smoking-related DNA methylation. We further performed MR steiger test to estimate the likely direction of causal estimate between DNA methylation and breast cancer. We also conducted colocalization analysis to evaluate whether smoking-related CpG sites shared a common genetic causal SNP with breast cancer in a given region. Results: We established four significant associations after multiple testing correction: the CpG sites of cg2583948 (OR = 0.94, 95%CI [0.91-0.97]), cg0760265 (OR = 1.07, 95%CI [1.03-1.11]), cg0420946 (OR = 0.95, 95%CI [0.93-0.98]), and cg2037583 (OR =1.09, 95%CI [1.04-1.15]) were associated with the risk of ER+ breast cancer. All the four smoking-related CpG sites had a larger variance than that in ER+ breast cancer (all p < 1.83× 10−11) in MR steiger test. Further colocalization analysis showed that there was strong evidence (based on PPH4 > 0.8) supporting a common genetic causal SNP between the CpG site of cg2583948 (with IMP3 expression [PPH4 = 0.958]) and ER+ breast cancer. There were no causal associations between smoking-related DNA methylation and ER- breast cancer. Conclusions: These findings highlight potential targets for the prevention of ER+ breast cancer. Tissue-specific epigenetic data are required to confirm these results.